2016
DOI: 10.1016/j.toxicon.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Unshared binding sites for Bacillus thuringiensis Cry3Aa and Cry3Ca proteins in the weevil Cylas puncticollis (Brentidae)

Abstract: Bacillus thuringiensis Cry3Aa and Cry3Ca proteins have been reported to be toxic against the African sweetpotato pest Cylas puncticollis. In the present work, the binding sites of these proteins in C. puncticollis brush border vesicles suggest the occurrence of different binding sites, but only one of them is shared. Our results suggest that pest resistance mediated by alteration of the shared Cry-receptor binding site might not render both Cry proteins ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Interestingly, previous studies have shown common binding sites for Cry3Ba, Cry3Ca, and Cry7Aa on C. puncticollis BBMV (Hernández-Martínez et al, 2014). Based on binding site interaction results of Cry3Aa and Cry3Ca proteins probably have two different binding sites that one of them is common between these two proteins (Hernández-Martínez et al, 2016). Thus, these observations along with the structural difference and subsequently different mechanisms of action of Cry23Aa to other conventional three-domain Cry proteins support Cry23Aa as a desirable candidate to be pyramided with Cry3Aa in Bt sweet potatoes to control of C. puncticollis effectively and delay the evolution of resistance.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, previous studies have shown common binding sites for Cry3Ba, Cry3Ca, and Cry7Aa on C. puncticollis BBMV (Hernández-Martínez et al, 2014). Based on binding site interaction results of Cry3Aa and Cry3Ca proteins probably have two different binding sites that one of them is common between these two proteins (Hernández-Martínez et al, 2016). Thus, these observations along with the structural difference and subsequently different mechanisms of action of Cry23Aa to other conventional three-domain Cry proteins support Cry23Aa as a desirable candidate to be pyramided with Cry3Aa in Bt sweet potatoes to control of C. puncticollis effectively and delay the evolution of resistance.…”
Section: Discussionmentioning
confidence: 91%
“…This rationale is based on the occurrence of different binding sites for the proteins that are pyramided, since if the pyramided proteins share a binding site in the midgut of the larva, a single mutation could confer cross-resistance to these proteins. By the aim of employing more than one Bt toxin, competition binding experiments have been previously performed by other authors in the midgut of C. puncticollis larvae and have provided models for the binding sites to predict or to explain patterns of cross-resistance or multiple resistance (Hernández-Martínez et al, 2014, 2016. As a result, the occurrence of shared binding sites for Cry3Ca, Cry3Ba, and Cry7Aa proteins to C. puncticollis brush border membrane vesicles (BBMV) has been described (Hernández-Martínez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation